2019
DOI: 10.1002/jgh3.12279
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of acute pancreatitis in octogenarians: A retrospective study

Abstract: Background and Aim Acute pancreatitis (AP) is a common disease, but data on outcomes in octogenarians are scarce in the literature. The aim of this study is to analyze results from patients aged 80 years old and over who were treated for AP at a single center. Methods Patients aged 80 years and older diagnosed with AP from April 2010 to October 2015 were considered. Demographics, American Society of Anesthesiologists (ASA) score, Charlson Comorbidity Index (CCI), serum biochemistry at 24 and 48 h after admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…It is not always easy to determine the correct risk-benefit balance of having surgery in this scenario. Previous reports have shown that many patients are deemed too frail to undergo either general anesthesia or any surgical procedure, and never undergo cholecystectomy following biliary pancreatitis (16). Conversely, a recent British national cohort study revealed that the CCI of the patients not having undergone surgery after biliary events was higher and, according to our results, gallbladder-related deaths were still significantly lower than all other causes of death in the non-surgical group (17).…”
Section: Discussioncontrasting
confidence: 42%
“…It is not always easy to determine the correct risk-benefit balance of having surgery in this scenario. Previous reports have shown that many patients are deemed too frail to undergo either general anesthesia or any surgical procedure, and never undergo cholecystectomy following biliary pancreatitis (16). Conversely, a recent British national cohort study revealed that the CCI of the patients not having undergone surgery after biliary events was higher and, according to our results, gallbladder-related deaths were still significantly lower than all other causes of death in the non-surgical group (17).…”
Section: Discussioncontrasting
confidence: 42%
“…Another study by Di Mauro et al found that a Charlson comorbidity index >4 was associated with higher disease severity and mortality in AP patients. They also suggested that, if feasible, cholecystectomy should be considered for elderly patients with gallstones (12). Murata et al demonstrated that comorbidities in elderly AP patients were associated with longer hospital stays and in-hospital mortality, with cardiovascular and renal diseases being particularly linked to mortality (13).…”
Section: Discussionmentioning
confidence: 99%